Niat Berwakaf Masyarakat Tarakan: Persepsi, Akses Terhadap Informasi Dan Pemahaman Norma Agama - Fathur Rahmansyah; Pitri Yandri (ITB AAS INDONESIA Surakarta, 2023)
The endowment is a significant religious practice and contributes to sustainable development. The community possesses a good understanding of religious norms related to the endowment, which involves genuine intentions, adherence to Sharia, and transparency. However, information about endowment in Tarakan City is limited, making it difficult to access details about endowment activities. Furthermore, the comprehension of religious norms and education about the benefits of endowment still need improvement. This study aims to analyze the influence of perception issues, access to information, and religious norms on the intention to endow in Tarakan City. The method employed in this research is quantitative, encompassing the entire population of Tarakan City, which, according to the Central Statistics Agency (BPS), amounts to 244,185 people. The sample for this study uses a purposive sampling technique with the Slovin formula, resulting in a sample size of 100 individuals. The data analysis technique in this research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) using the statistical software SmartPLS. The findings of this study indicate that Perception significantly influences the Intention to Endow due to the positive perception of endowment as a beneficial contribution to others or society at large, resulting in a stronger intention to engage in endowment actions. Access to Information, however, does not significantly affect the Intention to Endow, as the message might not be effectively conveyed or fail to capture the community's attention, potentially failing to trigger the formation of endowment intentions. Understanding of Religious Norms significantly influences the Intention to Endow, as endowment actions align with the practice of religious principles, and these norms can be a powerful driver in forming endowment intentions.